Representation of the Meaning of the Expression of Hijrah for Urban Muslim Community through Instagram: A Virtual Ethnographic Study - Royanulloh, Royanulloh; Taufiq, Thiyas Tono; Komari (Journal of Islamic Civilization, 2022)
The representation of the meaning of the expression of hijrah in the space of urban society is not only present in natural daily social life spaces but also in virtual spaces. The meaning of the expression hijrah in this study was traced through the hashtag hijrah (#hijrah). Hijrah is an interesting socio-religious phenomenon observed in urban Muslim communities. Hijrah between them is not just a spiritual phenomenon but has developed into a lifestyle trend. Hijrah has also developed into a social movement that forms a strong group identity. Through the virtual ethnographic method and the social representation theory approach, it was found that the expression of hijrah displayed on Instagram contains many meanings. First, hijrah is a persuasive tool in a business context, building account popularity and spreading religious values. Second, hijrah is a representation of self-existence. Urban communities express their physical and mental religious identity through content with #hijrah. Third, the expression through #hijrah also represents the values ​​of self-change in terms of style of dress, changes in pious behaviour with a high sense of spirituality, positive changes in social behaviour, the realization of a harmonious family, and sensitivity to religious education and religious history. Fourth, #hijrah represents the movement of an Islamic group, especially the Salafi community. Representasi makna ekspresi hijrah dalam ruang masyarakat urban tidak hanya hadir dalam ruang kehidupan sosial nyata sehari-hari, tetapi juga melalui ruang virtual. Makna ekspresi hijrah dalam penelitian ini ditelusuri melalui melalui hashtag hijrah (#hijrah). Hijrah merupakan fenomena sosial keagamaan yang menarik diamati pada masyarakat muslim urban. Hijrah di antara mereka tidak hanya sekedar fenomena spiritual, tetapi telah berkembang menjadi tren gaya hidup. Hijrah pun telah berkembang menjadi gerakan sosial yang membentuk identitas kelompok yang kuat. Melalui metode etnografi virtual dan pendekatan teori representasi sosial, didapatkan bahwa ekspresi hijrah yang ditampilkan melalui instagram mengandung banyak makna. Pertama, hijrah merupakan alat persuasif dalam konteks bisnis, membangun popularitas akun, hingga menyebarkan nilai-nilai keagamaan. Kedua, hijrah merupakan representasi eksistensi diri. Masyarakat urban perkotaan menuangkan identitas diri yang religius, baik secara fisik maupun batin, melalui konten-konten dengan #hijrah. Ketiga, ekspresi melalui #hijrah juga merepresentasikan nilai-nilai perubahan diri dalam hal gaya berpakaian, perubahan perilaku shaleh dengan rasa spiritualitas yang tinggi, perubahan perilaku sosial yang positif, perwujudan keluarga harmonis, serta kepekaan terhadap pendidikan agama dan sejarah agama. Keempat, #hijrah merepresentasikan gerakan suatu kelompok Islam, utamanya komunitas salafi.